2007
DOI: 10.1097/mca.0b013e32820588ae
|View full text |Cite
|
Sign up to set email alerts
|

No association of interleukin-6 gene polymorphism (-174 G/C) with premature coronary artery disease in a Turkish cohort

Abstract: We conclude that the IL-6 -174 G/C polymorphism is not associated with the risk of premature CAD, and does not contribute to cardiovascular risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 39 publications
3
19
1
1
Order By: Relevance
“…A study conducted in Tunisia with 418 CAD patients and 406 controls indicated that the IL-6 174G/C variant is not associated with an increased risk of CAD (Ghazouani et al, 2011). Another Turkish cohort study found that the IL-6 174G/C polymorphism does not contribute to the risk of cardiovascular disease (Sekuri et al, 2007). The strengths of this study include the fact that the allele frequencies for all IL-6 polymorphisms examined were similar to those previously reported for the Chinese population Shi et al, 2013).…”
Section: Discussionsupporting
confidence: 48%
“…A study conducted in Tunisia with 418 CAD patients and 406 controls indicated that the IL-6 174G/C variant is not associated with an increased risk of CAD (Ghazouani et al, 2011). Another Turkish cohort study found that the IL-6 174G/C polymorphism does not contribute to the risk of cardiovascular disease (Sekuri et al, 2007). The strengths of this study include the fact that the allele frequencies for all IL-6 polymorphisms examined were similar to those previously reported for the Chinese population Shi et al, 2013).…”
Section: Discussionsupporting
confidence: 48%
“…In addition, the frequency of the -174G/C (26.3) and -174C/C (2.4) genotypes in our patient group was lower than that in French or Irish (Belfast) population, as reported in the Etude Cas Temoin de l’Infarctus du Myocarde (ECTIM) study,25 or in German or Scottish populations 1926. Our finding of an apparent lack of association of -174G>C alleles and genotypes with CAD was reminiscent of an earlier case-control study among Tunisian patients of breast carcinoma (immuno-inflammatory disease) (n=305) and healthy control subjects (n=200), where a comparable distribution and frequency of -174G>C alleles and genotypes were noted between patient and control groups,27 which were also comparable to those reported by Sekuri et al in the Turkish population 28…”
Section: Discussionsupporting
confidence: 90%
“…After applying our inclusion/exclusion criteria, 19 articles were selected for inclusion in the final analysis [5,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. A diagram schematizing the selection process of identified and excluded articles with specification of reasons is presented in Fig.…”
Section: Search Results and Study Characteristicsmentioning
confidence: 99%